Efficacy of Local Minocycline Agents in Treating Peri-Implantitis: An Experimental In Vivo Study in Beagle Dogs - Sung-Wook Yoon; Myong-Ji Kim; Kyeong-Won Paeng; Kyeong Ae Yu; Chong-Kil Lee; Young Woo Song; Jae-Kook Cha; Ui-Won Jung (MDPI AG, 2020)
Background: Local delivery agents (LDA) have the advantage of delivering the antibiotics at high concentrations to the targeted sites. However, the constant flow of gingival crevicular fluids and saliva may restrict their efficacy. Therefore, the drug sustainability and pharmacodynamic properties of any proposed LDA should be evaluated. Methods: Four dental implants were placed unilaterally in the edentulous mandible of six beagle dogs. Peri-implantitis were experimentally induced using silk-ligatures. Each implant was randomly allocated to receive one of the following four treatments: (i) MC (Chitosan-alginate (CA) minocycline), (ii) MP (CA-without minocycline), (iii) PG (Polyacrylate-glycerin minocycline), and (iv) Control (mechanical debridement only). Mechanical therapies and LDAs were administered into the gingival sulcus two times at a 4-week interval. Drug sustainability as well as clinical, radiographical, and immunohistochemical (IHC) analyses were conducted to evaluate the efficacies of treatments. Results: Reduced mean probing depth was observed in all of the test groups after the second delivery. A minimal marginal bone level change was observed during the treatment period (MP (−0.06 ± 0.53 mm) to PG (−0.25 ± 0.42 mm)). The distribution of IHC cell marker analysis of all targeted antibodies ranged from 6.34% to 11.33%. All treatment outcomes between the test groups were comparable. A prolonged retention of LDA was observed from CA microspheres (MC and MP) at both administrations (p < 0.017) and prolonged sustainability of bacteriostatic effect was observed from MC compared to PG after the second administration (p < 0.05). Conclusions: Prolonged retention of CA microspheres was observed and the longer bacteriostatic effect was observed from the MC group. Mechanical debridement with adjunct LDA therapy may impede peri-implantitis progression, however, prolonged drug action did not lead to improved treatment outcome.